Early response predicts a sustained response to eluxadoline in patients with irritable bowel syndrome with diarrhoea in two Phase 3 studies. Issue 10 (22nd March 2017) - Chey, W. D.; Dove, L. S.; Andrae, D. A.; Covington, P. S.
Abstract : Summary: Background: The mixed μ‐ and κ‐opioid receptor agonist and δ‐opioid receptor antagonist, eluxadoline, is licensed in the USA for the treatment of irritable bowel syndrome with diarrhoea (IBS‐D), based on the results of two large Phase 3 clinical trials. Aim: To understand the time course of treatment benefits with eluxadoline by comparing responder rates over the first month of treatment with responder rates over longer treatment intervals. Methods: In this post hoc analysis of two Phase 3 studies, composite and adequate relief (AR) responder rates were calculated over month 1 and patients were stratified by their responder status. Cumulative counts over subsequent intervals (months 1–3, months 1–6, months 2 through 6) were tallied. Results: The studies randomised 2428 patients. Over month 1, 24.6%, 22.8% and 12.5% of patients were composite responders with eluxadoline 100 mg, eluxadoline 75 mg and placebo respectively. For month 1 responders, 77.8% and 81.5% (over months 1–3) and 70.7% and 73.9% (over months 1–6) showed a continuous response with eluxadoline 100 mg and 75 mg respectively. [Correction added on 5 April 2017, after first online publication: The percentage for the responders over months 1–3 was previously wrong and has been corrected.] Of the month 1 nonresponders, <20% showed a response over months 1–3 or months 1–6. Similar results were seen for the analysis of proportions of AR responders over these time intervals. Conclusions: Over two‐thirds of patients who respond over the first month retain a positive response over 6 months of treatment with eluxadoline, indicating that early clinical response to eluxadoline is associated with sustained benefits for up to 6 months in patients with IBS‐D.